EDUKASI DENGAN PENDEKATAN PRINSIP DIABETES SELF MANAGEMENT EDUCATION (DSME) MENINGKATKAN PERILAKU KEPATUHAN DIET PADA PENDERITA DIABETES MELLITUS TIPE 2 - Nadia Rohmatul Laili; Yulis Setiya Dewi; Erna Dwi Wahyuni (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Diabetes Mellitus (DM) is one of the incurable cronic diseases. The patient’s dietary obedience is a principal component in diabetes treatment success. One of the efforts to increase dietary obedience behavior in type 2 Diabetes Mellitus patients is using a Diabetes Self Management Education (DSME) principles approach. Diabetes Self Management Education (DSME) is the ongoing process of facilitating knowledge, skill and ability necessary for diabetes self care. The purpose of this study was to analyze the influence of DSME principles approach toward the dietary obedience behavior that consists of knowledge, attitude, and practice aspects in patients with type 2 Diabetes Mellitus at Puskesmas Kebonsari Surabaya.Methods: A quasy experimental design was used in this study with 24 people as the sample which taken by using purposive sampling and divided into two groups (treatment and control group). A structured questionnaire and daily meal note for seven days were used to collect the data. The data were analyzed by using Wilcoxon signed rank test and Mann Whitney U test with significant level α≤0.05. Result: The results showed that there was an influence of DSME principles approach after being applied to the treatment group and control group toward the dietary knowledge with the value of p=0.004 and p=0.083 respectively, the attitude of dietary obedience with p=0.025 and p=0.083 and the dietary obedience practice with p=0.002 and p=0.564.Discussion: The study showed that DSME approach had a significant influence toward the dietary obedience behavior in type 2 Diabetes Mellitus patients. DSME principles approach used learning based on patient empowerment and behavior strategies. Ongoing support also contributed in maintaining progress achieved so that resulting dietary obedience behavior in type 2 Diabetes Mellitus patients. Larger respondents, more proper instruments and longer duration of study are needed to get a better results of the study concerning diabetic patient’s obedience in the future.